Pengaruh Kualitas Pelayanan Dalam Pengambilan Keputusan Penggunaan Jasa Layanan Taksi Kosti Melalui Kepuasan Konsumen Sebagai Variabel Intervening (Studi Pada Konsumen Taksi Kosti Semarang) - Artha Julianty Manik; Sudharto P Hadi (Jurnal Ilmu Administrasi Bisnis, 2017)
The main problem is decreased decision making in using Kosti taxi service. The driving factors predicted are consumer satisfaction and service quality.The purpose of this study is to identify the effect of service quality in decision making on using kosti taxi services based on consumer satisfaction through intervening variable. Type of research is explanatory research. Samples used is 100 respondents who are taxi customers Kosti Semarang.The sampling technique used is accidental sampling and purposive sampling. Data collection techniques are interviews, questionnaire and literature study . The technique of data analysis is validity test, reliability test, crosstab analysis, correlation coefficient, determination coefficient, simple regression test, multiple regression test, significance test (t-test) and simultaneous test (f-test) using IMB SPSS (Statistical Product and Service Solutions) 16.0 version.Based on the analysis shows that consumer satisfaction and service quality have an effect on decision making of using services. Service quality’s variable has bigger effect than consumer satisfaction on decision making on using services in the amount 61,6% than 45,4%            Recommendations for taxi service company Kosti Semarang is to increase consumer satisfaction especially in terms of passenger safety and better service quality.